1984
DOI: 10.3109/00365518409085377
|View full text |Cite
|
Sign up to set email alerts
|

Renin, Angiotensin II, Aldosterone, Catecholamines, Prostaglandins and Vasopressin. The Importance of Pressor and Depressor Factors for Hypertension in Pregnancy

Abstract: Scand J Clin Lab Invest Downloaded from informahealthcare.com by University of Sydney on 01/03/15 For personal use only. 51 Scand J Clin Lab Invest Downloaded from informahealthcare.com by University of Sydney on 01/03/15 For personal use only. *0° t 53 Scand J Clin Lab Invest Downloaded from informahealthcare.com by University of Sydney on 01/03/15 For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In a previous study [8] we found the same AVP level during normal pregnancy and in nonpregnant control subjects as in the present study. As in the present study, how ever, others have found high concentrations of AVP in umbilical arterial cord blood at the time of birth [3,5,9] and animal experiments have shown that the fetus is autonomic with respect to AVP secretion and the placenta impermeable to AVP [1,10,11], Hadeed et al [12] have suggested that intracranial pres sure elevation resulting from labor and birth stimulates AVP secretion in the fetus.…”
Section: Discussionsupporting
confidence: 58%
“…In a previous study [8] we found the same AVP level during normal pregnancy and in nonpregnant control subjects as in the present study. As in the present study, how ever, others have found high concentrations of AVP in umbilical arterial cord blood at the time of birth [3,5,9] and animal experiments have shown that the fetus is autonomic with respect to AVP secretion and the placenta impermeable to AVP [1,10,11], Hadeed et al [12] have suggested that intracranial pres sure elevation resulting from labor and birth stimulates AVP secretion in the fetus.…”
Section: Discussionsupporting
confidence: 58%
“…this biological effect in the maternal circulation, and the focus over the years has encompassed the reninangiotensin system [57][58][59][60][61], norepinephrine [62,63], vasopressin [64], prostaglandins [65], endothelin [20], cytokines [7], and others [66]. Since many investigators believed that the placenta is the source of the pressor agents, some studies also explored the concentration of numerous candidate mediators for 'toxic factors' of preeclampsia in the uterine vein, which represents blood exiting the uterus before gaining access to the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the increase in blood pressure could not be elicited by re-transfusion 6 weeks postpartum, the authors concluded that patients with pre-eclampsia had increased sensitivity to pressor agent(s) which lasted about 1 week after delivery, but not as long as 6 weeks. Thereafter, considerable effort was devoted to the identification of the pressor agent responsible for this biological effect in the maternal circulation, and the focus over the years has encompassed the renin-angiotensin system [47][48][49][50] , noradrenaline (norepinephrine) 51,52 , vasopressin 53 , prostaglandins 54 , endothelin 55 and others 56 .…”
Section: Discussionmentioning
confidence: 99%